Soil microbiological properties and available nitrogen for corn in monoculture and intercropped with forage - Coser, Thais Rodrigues; Ramos, Maria Lucrécia Gerosa; Figueiredo, Cícero Célio de; Carvalho, Arminda Moreira de; Cavalcante, Eduardo; Moreira, Moacir Kildery dos Reis; Araújo, Patrícia Silva Melo; Oliveira, Sebastião Alberto de (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effects of corn (Zea mays) in monoculture and intercropped with forage on soil microbiological properties and nitrogen availability under no-tillage in the Cerrado (Brazilian savanna). The experiment was carried out from the 2007/2008 to the 2010/2011 crop season, in a Latossolo Vermelho-Amarelo distrófico (Typic Haplustox). A randomized complete block design with three replicates was used, with the following treatments: corn in monoculture; corn intercropped with Panicum maximum; corn intercropped with Urochloa humidicola; P. maximum in monoculture; and U. humidicola in monoculture. Soil samples were taken at 0.00–0.05, 0.05–0.10, 0.10–0.20, and 0.20–0.30-m soil depths, in the begining and in the end of the last crop season. The intercropping systems of corn increased soil nitrogen availability, but did not alter total nitrogen and organic carbon contents in the soil, when compared to corn in monoculture. Corn intercropped with P. maximum increased soil microbial biomass nitrogen and microbial nitrogen quotient, in comparison to corn in monoculture, as well soil as microbial biomass carbon in the surface soil layer, when compared to corn intercropped with U. humidicola